Legal Review of Sharia Transactions in Modern Economics - Fauziah Zulfa Nur Laila; Muthoifin (al-Afkar, Journal For Islamic Studies, 2025)
In the era of rapid technological development and globalization, the modern economy presents new challenges in terms of transactions following sharia economic principles. Islam, as a timeless universal religion that regulates faith, sharia and morals comprehensively, exists as a guide for every Muslim in carrying out business transaction activities. Transaction comes from the English "transaction". Often in Arabic, it is called al-Mu'amalat. Thus transaction is another word for al-Mu'amalat. In the context of fiqh science, the science of fiqh that studies al-Mu'amalat is called fiqh al-Mu'amalat. Fiqh al-Mu'amalat in a certain sense covers a very broad field, for example law regarding transactions, sanctions, criminal penalties, guarantees, and other laws that regulate relationships between humans and organizations. Sharia economics also offers an approach based on Islamic principles, which include the principles of justice, transparency and sustainability.